PKM Strategi Pemasaran Produk Untuk Meningkatkan Ketahanan Pangan Desa Rancasumur Serang Banten - Akbar, Mada Faisal; Sudarsono, Agus; P, Purwanti (Yayasan Daarul Huda Kruengmane, 2024)
Product Strategy is intended to influence consumers, both in the short and long term. In the short term, the new product strategy is intended to influence consumers to try the product. In the long term, product strategy is designed to develop loyalty to the brand and gain a large market share. The most decisive aspect of designing a product strategy involves analyzing the consumer-product relationship. This means that consumer affection, cognition and behavior regarding products and the environment must be carefully considered when introducing new products and must be monitored throughout a product's life cycle. Food is an important and strategic commodity for the Indonesian nation considering that food is a basic human need that must be met by the government and society together as mandated by Law Number 7 of 1996 concerning food. In this law, it is stated that the government carries out regulation, guidance, control and supervision, while the community carries out the production and supply, trade, distribution processes and acts as consumers who have the right to obtain food that is sufficient in quantity and quality, safe, nutritious, diverse, equitable and affordable. by their purchasing power.